Zero-inflated Conway-Maxwell Poisson Distribution to Analyze Discrete Data - Sim, Shin Zhu; Gupta, Ramesh C.; Ong, Seng Huat (De Gruyter, 2018)
In this paper, we study the zero-inflated Conway-Maxwell Poisson (ZICMP) distribution and develop a regression model. Score and likelihood ratio tests are also implemented for testing the inflation/deflation parameter. Simulation studies are carried out to examine the performance of these tests. A data example is presented to illustrate the concepts. In this example, the proposed model is compared to the well-known zero-inflated Poisson (ZIP) and the zero-inflated generalized Poisson (ZIGP) regression models. It is shown that the fit by ZICMP is comparable or better than these models.